(untitled) (Revista Lusófona de Educação, 2025)
The objective of this work is to identify the cognitive processes from Bloom’s taxonomy as revised by Anderson and Krathwohl, which are present in the assessment criteria for Mathematics in one of Spain’s primary education curricula (specifically, that of the Autonomous Community of Galicia) and in the learning objectives of the Mathematics curriculum for the corresponding first six years of Basic Education in Portugal. The aim is to compare the distribution of these processes within each country and between them, in order to determine and contrast the cognitive demands required by both the criteria and the objectives. These educational periods correspond to students aged 6 to 12. A preliminary document analysis is conducted, reviewing the current educational legislation in both countries, and a mixed methodology is used: qualitative regarding the cognitive processes, and quantitative for the statistical tests performed. A total of 294 assessment criteria and 619 learning objectives are reviewed. The study concludes that the Spanish criteria and Portuguese objectives show different profiles and progression patterns over the educational period studied, with significant differences in the distribution of cognitive processes among topics in the Portuguese curriculum. On a scale from 0 to 10, the cognitive demand level is estimated at 4.6 in Portugal and 4.3 in Spain.